Education and health professionals training programs for people with type 2 diabetes: a review of quality criteria - Silke Kuske; Andrea Icks; Jelka Zaletel; Ulrike Rothe; Jaana Lindström; Monica Sørensen; Marina Maggini (Istituto Superiore di Sanità, 2015)
OBJECTIVE. To contribute to the development of a set of quality criteria for patient education and health professionals training that could be applied in European countries. METHODS. Literature review quality criteria, pre-selection based on a comparison of the criteria, peer group and expert based selection of the criteria. RESULTS. 14 quality criteria were selected: goals, rationale, target group, setting, scheduling of the education/training sessions, environmental requirements, qualification of the trainers/educators, core components of the educator/trainer's role, curriculum, education methods, education didactics, monitoring of the effectiveness and quality of the program, implementation level and source of funding. DISCUSSION. A set of preliminary quality criteria for patient education and health professionals training was developed, which could be applied in European countries.